2013
DOI: 10.7314/apjcp.2013.14.9.5379
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Osteogenic Differentiation in Stromal Cells of Giant Cell Tumour of Bone by Zoledronic Acid

Abstract: Therapeutic effects of zoledronic acid (ZOL) on giant cell tumour of bone (GCT) have been proven. Apoptosis induction was considered to be one of the mechanisms of ZOL tumour inhibition. In this study, we presented the possibility of an osteogenic differentiation stimulation mechanism of ZOL and further investigated dosage and time effects. We treated stromal cells of GCT (GCTSC) with ZOL for 48 hours at different concentrations (0 μM, 0.01 μM, 0.1 μM, 1 μM, 5 μM, 30 μM) and assessed apoptotic and osteogenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Histological analysis of H&E and TRAP staining revealed that the patient-derived GCTB cells survived, and caused an osteolytic reaction in the bone environment. Furthermore, previous studies have reported that stromal cells can differentiate into mature osteoblasts, adipocytes and chondrocytes (11,12,(33)(34)(35)(36). Observed differences between the results of the present study and others may indicate that stromal cells undergo multidirectional differentiation, which may be influenced by the tissue microenvironment.…”
Section: Discussioncontrasting
confidence: 86%
“…Histological analysis of H&E and TRAP staining revealed that the patient-derived GCTB cells survived, and caused an osteolytic reaction in the bone environment. Furthermore, previous studies have reported that stromal cells can differentiate into mature osteoblasts, adipocytes and chondrocytes (11,12,(33)(34)(35)(36). Observed differences between the results of the present study and others may indicate that stromal cells undergo multidirectional differentiation, which may be influenced by the tissue microenvironment.…”
Section: Discussioncontrasting
confidence: 86%
“…We suggest that systemic chemotherapy be considered if local control fails following radiotherapy or distal metastases are identified. Studies have indicated that topical or systemic use of bisphosphonates may present a novel adjuvant therapy for GCT by inducing apoptosis of stromal tumor cells and stimulating osteogenic differentiation of the remaining tumor stromal cells following surgery ( 20 22 ).…”
Section: Discussionmentioning
confidence: 99%
“… 1-4 BPs are currently administered as anti-resorptive medications to manage hypercalcemia of malignancy, skeletal-related events accompanying bone metastases in the context of solid tumors, lytic lesions in multiple myeloma, Paget’s disease of the bone, osteogenesis imperfecta, osteoporosis, and osteopenia. 5-12 BPs have high affinity for sites of active bone remodeling, where they suppress, both directly and indirectly, osteoclast-mediated bone resorption. 13-15 The inhibitory effects of BPs on the boneresorbing activity and on the development, proliferation and viability of macrophage lineage cells have been also reported.…”
Section: Introductionmentioning
confidence: 99%